Overcoming Stunting in Adolescents at Risk of Anemia in the Kapas District, Sukowati Village, Bojonegoro (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a serious problem, namely the failure to grow a child or toddler due to chronic malnutrition due to infectious disease disorders, if allowed to greatly affect intelligence. In 2021 the Bojonegoro government prioritizes the handling of stunting, there must be joint work. Data from the 30% National survey are both important issues to deal with together. Prevention of stunting starts in the womb. Habits of teenagers, most importantly iron affects adolescence, don't forget 4 Healthy 5 Perfect or fill my plate activities. The health of a young woman as a prospective mother and at the same time as the nation's successor needs to be a major concern. Adolescents are humans in the transition stage to adulthood with rapid growth associated with iron fulfillment. Insufficient iron intake can cause anemia. The national incidence of anemia at the age of 1 year, 5-11 years, and 15-24 years were 21.7%, 26.4%, and 18.4%, respectively. Factors causing stunting include nutritional intake and parenting patterns for toddlers from caregivers who must be given good and sufficient knowledge. Smoking is also one of the causes of stunting, because it affects the economic pattern of a family. Factors that influence anemia in adolescent girls are lack of consumption of foods containing iron, menstruation, consumption of blood-added tablets, and consumption of tea or coffee after eating. Giving blood supplement tablet therapy is one of the important efforts to prevent and overcome anemia due to iron deficiency. The purpose of this service is to overcome the problem of anemia in adolescent girls based on the results of a qualitative research analysis of the factors causing the problem of low consumption of Fe tablets. This activity has been carried out in Sukowati village, Kapas sub-district, Bojonegoro district with the target of junior high, high school, and vocational school students in Sukowati village as anemia prevention ambassadors. Community empowerment strategies have been carried out in the form of socialization, FGD for PKK mothers and the formation of anemia prevention communities, until finally achieving: 1) raising public awareness, in this case schools and students of SMP, SMA, SMK in Sukowati Village about the importance of preventing anemia, 2) then motivate and enable the community with prevention education and training processes